Nodular Episcleritis in a Boy with Pulmonary Tuberculosis - Rizki Matta Handayani; Niken Indah Noerdiyani; Indriani Kartika Dewi (Vision Science and Eye Health Journal, 2022)
Introduction: Episcleritis is an acute inflammation of the vascular connective tissue between the conjunctiva and the sclera’s surface, which can be found unilateral and bilateral. Tuberculosis (TB) is one of the systemic infectious diseases that cause morbidity in developing countries and can affect the ocular area known as ocular tuberculosis There are still limited cases of ocular tuberculosis studies, specifically tubercular nodular episcleritis in adolescents. This case report aims to expose nodular episcleritis in pediatric tuberculosis patients in Indonesia. Case Presentation: A 16-year-old boy came to the Community Eye Health Hospital East Java with superior bilateral eye redness and pain with normal visual acuity. He underwent advanced anti-tubercular treatment for the last nine months. The best corrected visual acuity (BCVA) of both eyes was 6/6. Slit-lamp biomicroscopy (SLB) examination found the dilation of blood vessels located on the superior episclera accompanied by a firmly bordered, fixed, pink nodule, diameter ± 1.5 mm located at 12 o’clock in bilateral bulbar conjunctiva. Based on anamnesis and physical examination, the diagnosis of nodular episcleritis et causa pulmonary TB was established. Topical corticosteroids and artificial tears eyedrops were given in both eyes for five weeks, and continuing anti-tubercular treatment was performed. Conclusion: It is necessary to investigate the primary cause of episcleritis by eliminating underlying systemic diseases. Herein, we present a rare case of nodular episcleritis in an adolescent with pulmonary tuberculosis who responded very well to anti-tubercular treatment with topical corticosteroid and artificial tears eye drops.